2023
DOI: 10.1183/23120541.00558-2022
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dual IQOS and cigarette smoke exposure on airway epithelial cells: implications for lung health and respiratory disease pathogenesis

Abstract: BackgroundCigarette smoking (CS) remains the primary cause of chronic lung diseases. After a steady decline, smoking rates have recently increased especially with the introduction of newer electronic nicotine delivery devices, and it is also emerging that dual or poly product usage is on the rise. Additionally, with the introduction of IQOS (a heated tobacco product) globally, its impact on human health needs to be investigated. In this study we tested if dual exposure (CS+IQOS) is detrimental to lung epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Transcriptomic changes associated with oxidative stress were more prominent at 4 hours of exposure, suggesting early adaptive mechanisms and antioxidant responses that varied based on the intensity of exposure [ 13 ]. Moreover, in a mouse model exposed to an intensive puffing regime of HTPs, characterized by 5 hours of exposure per day over a 2-week period, significant increases in proinflammatory cytokines, chemokines, and CD4+RORγt + T cells were observed in bronchoalveolar lavage fluid [ [25] , [26] , [27] , [28] , [29] ]. These findings shed light on the underlying cellular mechanisms contributing to various inflammatory pathologies like organizing pneumonia in our case, respiratory infections, inflammation, autoimmune diseases, asthma, and chronic obstructive pulmonary disease (COPD).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic changes associated with oxidative stress were more prominent at 4 hours of exposure, suggesting early adaptive mechanisms and antioxidant responses that varied based on the intensity of exposure [ 13 ]. Moreover, in a mouse model exposed to an intensive puffing regime of HTPs, characterized by 5 hours of exposure per day over a 2-week period, significant increases in proinflammatory cytokines, chemokines, and CD4+RORγt + T cells were observed in bronchoalveolar lavage fluid [ [25] , [26] , [27] , [28] , [29] ]. These findings shed light on the underlying cellular mechanisms contributing to various inflammatory pathologies like organizing pneumonia in our case, respiratory infections, inflammation, autoimmune diseases, asthma, and chronic obstructive pulmonary disease (COPD).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were identified that utilized bubbled smoke/aerosol extracts to compare the in vitro toxicological effects of HTP aerosol with cigarette smoke in respiratory tract cell lines [ 40 , 77 , 78 ]. In the first study, the effects of liquid extracts of aerosol produced from both the Glo and IQOS HTP on oxidative stress in a human lung fibroblast cell line were investigated [ 77 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the third study, human bronchial epithelial (BEAS-2B) cells were used to investigate the effect of dual product use on a range of in vitro endpoints, including cell viability and oxidative stress [ 78 ]. Liquid extracts were produced by bubbling aerosol or smoke from one IQOS HTP consumable or one Marlboro Red cigarette into phosphate-buffered saline, and the resulting stock solution was used to create serial dilutions for testing.…”
Section: Reviewmentioning
confidence: 99%
“…Various studies have been conducted to estimate the potential risk of HTPs. The main interests of researchers regarding HTPs are the toxicological concerns and their risk in the respiratory tract ( Dempsey, 2023 , Saha, 2023 , Muratani, 2023 ) because HTPs are inhalable products and have similar behavior of use as cigarettes. To date, several reports related to the reduced risk potential of HTPs for CVD have been published.…”
Section: Introductionmentioning
confidence: 99%